2016
DOI: 10.1159/000445643
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Activation Attenuates IL-6 and TNF-α Pathways in Hippocampus of Rats Following Transient Global Ischemia

Abstract: Background/Aims: This study was to examine the role played by hypoxia inducible factor-1 (HIF-1α) in regulating pro-inflammatory cytokines (PICs) pathway in the rat hippocampus after cardiac arrest (CA) induced-transient global ischemia followed by cardiopulmonary resuscitation (CPR). Those PICs include interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Methods: A rat model of CA induced by asphyxia was used in the current study. Following CPR, the hippocampus CA1 region was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 32 publications
3
39
0
1
Order By: Relevance
“…It should also be noted that we determined the levels of IL-1β, IL-6 and TNF-α as well as their respective receptors in the specific brain regions, cortex and hippocampus CA1 region. Those specific brain regions were selected in our study because expression of PICs and their receptors is upregulated in those regions following CA in rats and in general they are also more related to neurological deficits after cerebral ischemia than other brain regions [18, 20]. Our results showed that CA amplifies the levels of IL-6 and TNF-α in addition to IL-1β, which is consistent with the previous report [11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It should also be noted that we determined the levels of IL-1β, IL-6 and TNF-α as well as their respective receptors in the specific brain regions, cortex and hippocampus CA1 region. Those specific brain regions were selected in our study because expression of PICs and their receptors is upregulated in those regions following CA in rats and in general they are also more related to neurological deficits after cerebral ischemia than other brain regions [18, 20]. Our results showed that CA amplifies the levels of IL-6 and TNF-α in addition to IL-1β, which is consistent with the previous report [11].…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have demonstrated that hypoxia inducible factor-1 (HIF-1) subtype HIF-1α is expressed in the brain tissues including the neocortex and hippocampus and engaged in neuronal apoptosis after induction of global ischemia [14-17]. In particular, a recent study using this model has further demonstrated that CA increases IL-1β, IL-6 and TNF-α and upregulates their receptors IL-1R, IL-6R and TNFR1 in the hippocampus [18]. Systemic activation of HIF-1α attenuates these exaggerated PIC signal pathways [18], and as a result neuronal apoptosis and neurological deficits induced by CA are attenuated [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that both passive and pre-ischemic exercise suppressed the apoptosis and reduced neurons loss in the periinfarct area via upregulating expression of Bcl-2 and maintaining the balance ratio of Bax/Bcl-2 [37-39]. Except for Bcl-2 family, caspase-3 is one of the most important downstream executors in the mitochondrial apoptotic pathway, which is considered as an indicator of neuronal apoptosis [40]. Previous studies have demonstrated that deletion and inhibition of caspase-3 provided neuroprotection through mediating neuronal death and rendering neurons resistant to ischemic injury in vivo and in vitro [41].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-10) are involved in brain cell apoptosis and necrosis after I/R [47-50]. Reducing the inflammatory factors could protect the brain from IRI.…”
Section: Discussionmentioning
confidence: 99%